2021
DOI: 10.1038/s41378-021-00244-3
|View full text |Cite
|
Sign up to set email alerts
|

Acoustofluidic separation enables early diagnosis of traumatic brain injury based on circulating exosomes

Abstract: Traumatic brain injury (TBI) is a global cause of morbidity and mortality. Initial management and risk stratification of patients with TBI is made difficult by the relative insensitivity of screening radiographic studies as well as by the absence of a widely available, noninvasive diagnostic biomarker. In particular, a blood-based biomarker assay could provide a quick and minimally invasive process to stratify risk and guide early management strategies in patients with mild TBI (mTBI). Analysis of circulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…Some studies already suggest that finding higher levels of glial-derived exosomes in blood could be used as a disease biomarker in TBI ( Manek et al, 2018 ; Mondello et al, 2020 ; Wang et al, 2021 ), EAE ( Willis et al, 2017 ), and alcohol abuse ( Kodidela et al, 2020 ). Therefore, if new studies arise in the field, connecting number, glial origin and cargo, their assessment would be expected to be useful as a real biomarker for disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies already suggest that finding higher levels of glial-derived exosomes in blood could be used as a disease biomarker in TBI ( Manek et al, 2018 ; Mondello et al, 2020 ; Wang et al, 2021 ), EAE ( Willis et al, 2017 ), and alcohol abuse ( Kodidela et al, 2020 ). Therefore, if new studies arise in the field, connecting number, glial origin and cargo, their assessment would be expected to be useful as a real biomarker for disease.…”
Section: Discussionmentioning
confidence: 99%
“…Different strategies have been used for identifying the presence of glial-derived exosomes in body fluids, such as plasma and CSF. Some of them have evaluated the presence of GFAP (for astrocyte origin) or isolectin B4 (IB4) (for microglial origin) in total purified exosomes by either western blot of flow cytometry ( Joshi et al, 2014 ; Willis et al, 2017 ; Kodidela et al, 2020 ; Mondello et al, 2020 ; Wang et al, 2021 ). Others have done proteomic analysis, finding GFAP expression as well ( Manek et al, 2018 ), while some have identified glial exosomes by ELISA sandwich, combining glutamate aspartate transporter (GLAST) and CD81 in plasma samples ( Ohmichi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In many biological and medical applications, the efficient separation of particles or cells based on microfluidic approaches provides a convenient, miniaturized, automated, and reliable method for disease diagnosis, drug screening, , and cell analysis. The microfluidic technology is also called lab-on-a-chip. Through the design of ingenious microchannel structures and actuators, the entire cell and particle separation process can be scaled down to a small chip.…”
Section: Introductionmentioning
confidence: 99%
“…In many biological and medical applications, the efficient separation of particles or cells based on microfluidic approaches provides a convenient, miniaturized, automated, and reliable method for disease diagnosis, 1 3 drug screening, 4 , 5 and cell analysis. 6 8 The microfluidic technology is also called lab-on-a-chip.…”
Section: Introductionmentioning
confidence: 99%
“…and have added to the expanding knowledge of the brain response to mild to moderate TBI by increasing the understanding of mechanisms, pathological outcomes, and therapeutic interventions after injury [16][17][18][19][20][21][22] . Adapting closedhead TBI models for mice allows researchers to increase throughput and leverage transgenic approaches for mechanistic studies.…”
Section: Introductionmentioning
confidence: 99%